Issue Information. (1st December 2022) - Unknown
Abstract : Causal pathways associated with graft failure and death, taken from the article "Rationale for the IMAGINE study for chronic active antibody‐mediated rejection (caAMR) in kidney transplantation" (page 38‐44) Abstract : Causal pathways associated with graft failure and death, taken from the article "Rationale for the IMAGINE study for chronic active antibody‐mediated rejection (caAMR) in kidney transplantation" (page 38‐44)